Concentración de Biol a base de guano de isla en la producción de follaje del Coriandrum Sativum. culantro. Loreto, 2025 - Franco Pachas, Jesus Milciades (2025)
In the Amazon region, cilantro leaves are widely used in village meals because they are highly aromatic and have many nutritional properties. Research is needed to improve the yield of this crop. This research, entitled "CONCENTRATION OF BIOL BASED ON ISLAND GUANO IN THE PRODUCTION OF FOLIAGE OF Coriandrum sativum. CILANTRO. LORETO, 2025," is published. The design used was an ANOVA with four treatments and four repetitions with the following treatments: T0 (control), T1 (10% Biol + 90% water), T2 (20% Biol + 80% water) and T3 (30% Biol + 70% water), reaching the following results regarding the dependent variable of plant height that treatment T3 (30% Biol + 70% water) with 26 cm, treatment T2 (20% + 80%) with 24.48 cm, T1 (10% Biol + 90% water) with 22.91 cm and T0 (control) with 17.83 cm., regarding the dependent variable of root length that treatment T3 (30% Biol + 70% water) with 11.07 cm. Regarding the dependent variable of bundle weight/m2, the T3 treatment (30% BioL + 70% water) achieved 2.91 kilos/m2. The yield achieved with the T3 treatment (30% BioL + 70% water) was 17,460 kilos/ha of 6,000 m2.